USING FUZZY MULTI CRITERIA DECISION MAKING APPROACH FOR THE EVALUATION OF EFFICIENCY OF FREIGHT RAIL OPERATORS - Blagojevic, Aleksandar; Veskovic, Slavko; Stojic, Gordan; Stojanova, Iskra (Horizons - International Scientific Journal, 2018)
The state railway deficit is enormous, and the issue of the efficiency of railway companies has become a reality in economic and political debates. Permanent rail deficits also indicate that the overcapacity in the entire industry, with the lack of efficiency of railways under the state administration, could be the main reason for the insufficient or negative return of invested capital. In times when there is a large public debt in the entire world, the state has a natural interest in adapting railway companies and making the capital allocated to them profitable. It is therefore of particular importance to restructure the railways and develop their competitive capabilities. The European Union is embarking on a comprehensive process of restructuring and commercialization of railway transport, which enables the reaffirmation and improvement of the quality of railway services and the efficiency of railways.The main objective of the European policy of rail transport is the development of a single railway area. The opening of railway sector to market competition imposes that railway undertakings behave like any other modern enterprises in other markets and in other industries. It means, they must constantly develop and maintain competitive advantages, and be better than others. In today's very intense competition conditions this is the most difficult to achieve. The railway undertakings are challenged to find optimal solutions to operate efficiently and effectively, in order not only to survive on the transport market, but alsoto develop and maintain a competitive advantage. A wide range of criteria can be studied when it comes to the efficiency of railway undertakings. In most cases there are several criteria that are often mutually conflicting. The aim of this study is to define and evaluate the criteria that influence the efficiency of railway undertakings and increasing of their competitive ability and to propose a model for the evaluation of the effectiveness and efficiency of railway undertakings in order to increase the competitive ability. To solve the problem of indicators selection, it was experimented with one of the most used methods for making decisions today - Fuzzy analytic hierarchy process(FAHP).